World Literature and Periphery: A Distant Reading of Milton Hatoum’s The Brothers - Jurdi, Erika (Université d'Ottawa | University of Ottawa, 2020)
This essay uses the novel The Brothers, by Brazilian writer Milton Hatoum, as an example of how literature from periphery countries can be read as world literature by readers of core countries or of cultural centres, based on the theoretical framework of the world system theory, by Wallerstein. which divides the world in a industrialized capitalist core, and dependent periphery and semi-periphery countries. By using the model of Moretti’s world literary system to exemplify how some literary production is being left out of the academic conversation on world literature, I propose a distant reading of Hatoum’s novel to show that there is nothing intrinsically alien or completely “regional” to the text which would justify its exclusion from the category of world literature. The text does not diminish its cultural and social background to conform to a Eurocentric view of the world, instead it invites us to reflect critically on cultural hegemony, born of imperial colonization, that tends to relegate works from peripheral areas to circulation at the margins of the Western world.
Keywords: Milton Hatoum; periphery; world literature